A European Mechanism for the Issuance and Initial Distribution of Debt Securities - Georgios Pavlidis (Intereconomics)
Abstract Although the European Union (EU) has implemented initiatives and common rules regarding securities settlements, no similar integration initiatives have been proposed for the issuance and initial distribution of debt securities. The EU does not function as a single market given that issuers of euro debt instruments still have to use multiple and non-harmonised channels and procedures. A harmonised European framework for the issuance and initial distribution of debt securities or the establishment of a new European market infrastructure service is widely considered a way to create a deep and liquid single market for debt instruments. While such a paradigm shift promises significant improvements compared with the existing debt issuance and distribution landscape, a hasty and poorly designed public intervention would risk distorting the market, thereby increasing complexity and bringing more fragmentation.